Comparison between Legiolert and real time PCR in the detection of Legionella pneumophila from environmental water samples - Arrigo, Ignazio; Serra, Nicola; Mariyam, Laiba; Sarvandani, Mandana Mirzajani; Tricoli, Maria Rita; Palermo, Roberta; Diquattro, Orazia; Gallina, Giuseppe; Di Carlo, Paola; Firenze, Alberto; Palermo, Mario; Giammanco, Anna; et al. (PLOS ONE, 2025)
Legionellosis is a resvpiratory disease of public health concern. Identification and quantification from environmental sources are crucial for identifying outbreak origins and providing information for risk assessment and disease prevention. Legionella pneumophila is typically detected and quantified using the culture method, which is considered the gold standard, but it has some critical limitations. The Legioler/Quanti-Tray test can be used as an alternative method to simplify the testing process and reduce the time required to obtain the result. In this study, we compare the new liquid culture method Legiolert™ and real-time PCR with traditional plate culture, assessing the performance of PCR and culture methods for detecting L. pneumophila in potable water samples. We analyzed 75 environmental water samples in parallel using the Standard method (ISO 11731:1998), Legiolert, and real-time PCR for the detection of L. pneumophila. The McNemar test was used to assess the difference in accuracy between the Legiolert and real-time PCR methods, showing that the culture test was more accurate than the molecular biology method. The study confirmed that the Legiolert test is specific, easy to use, and may serve as an alternative to standardized procedures for the quantification of L. pneumophila in water. However, due to its high sensitivity and rapid result acquisition, we believe it could be used as a screening tool to quickly ascertain the absence of the microorganism.